Analysis of Standard Operational Procedure Submission of Special Ceiling For Sales Division - Trisninawati; Zaid Amin; Heriyanto; Darwin (PT Mattawang Mediatama Solution, 2023)
This study aims to analyze the standard operating procedure (SOP) for filing an exceptional ceiling for the sales division at PT. Semen Baturaja (Persero) Tbk. This study uses a qualitative research design with a case study approach. Data was collected through interviews, document analysis, and observation of the SOP submission process for the sales division at PT. Semen Baturaja (Persero) Tbk. This study's findings are whether the Standard Operational Procedure for Submission of Special Ceilings has been going well or not. Standard operating procedures that are running well are shown in the Special SOP for Ceiling Submission; this can happen because it is in the preparation process so that, in practice, SOPs can be easily understood and also efficiently implemented by distributors. While implementing the main things in the Standard Operating Procedures is good because it has been appropriately implemented in every job, there's just no workflow in the Sales Division. In addition, there are due distributor receivables, so it becomes an obstacle for distributors to apply for a Special Ceiling according to the Standard Operating Procedure (SOP). This research contributes to the literature on SOPs by highlighting the importance of well-defined and effectively implemented SOPs in the context of the sales division of PT. Semen Baturaja (Persero) Tbk. In addition, this study provides insight into the challenges and factors that may influence SOP implementation in this environment. Practical implications for the management of PT. Semen Baturaja (Persero) Tbk and sales division. The findings indicate the need for more detailed and simplified SOPs for special ceiling proposals to improve process efficiency. In addition, this study recommends that companies provide adequate training and support for employees involved in the process. This research is limited to one case study at PT. Semen Baturaja (Persero) Tbk and these findings may not be generalizable to other companies or industries. In addition, this study does not evaluate the impact of implementing improved SOPs on sales division performance. Future research can explore these areas and assess the effectiveness of various strategies to improve the unique ceiling application process in sales divisions in peer companies in Indonesia.